The Effect of Health Education on Adolescent Knowledge About the Drugs Abuse - Devi, Silvia; Anwar, Sufyan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Drug abuse is currently very impressive in Indonesia. Now drugs are widely used by all walks of life, even children and adolescents. This study aims to prove the effect of health education on adolescent knowledge about the dangers of drugs. This study uses a pre-experimental one group pretest-posttest design type. By using quantitative research methods by distributing questionnaires before providing health education and after health education to see the level of knowledge about drugs. Class XII students of SMA Negeri 6 ABDYA became the research population visited by 120 students and 30 students were randomly selected as research samples. The measurement of knowledge about the dangers of drugs was carried out twice, namely the first measurement before the intervention was given and the second measurement after the intervention was given. The results showed that adolescents with good knowledge in the first measurement were only 3.3% with an average value of 41.83% and in the second measurement increased to 73.3% with an average value of 72.83%. Paired Simple T-Test statistical test found a significant effect between intervention through education on adolescent knowledge about the dangers of drugs (P value < 0.001). Providing knowledge about the dangers of drugs plays an important role in increasing adolescent knowledge, so that adolescents can know and understand well about the dangers of drug use.